Hostility in the House of God : An Investigation of the Opponents in 1 and 2 Timothy - Thornton, Dillon T. (Book collections on Project MUSE., 2016)
Virtually all scholars acknowledge the presence of opponents in 1 and 2 Timothy, but there is considerable disagreement over the identity of these opponents and the author's way of handling them. In this volume, Thornton provides a critique of a number of extant theories, including ""Gnostic, "" Jewish, and proto-Montanist identifications, and develops a rigorous methodology for unmasking the opponents who appear in these letters. He argues that the opponents came from within the Christian community in Ephesus and that their teaching is best described as an erroneous eschatological position tha.